Efficiency of Intra-Articular Platelet-Rich Plasma Injection in Grade I and Grade II Osteoarthritis in the Knee Joints: A Longitudinal Study - Khadim Khawaja, Imran Khan Maher, Zulfiqar Ali Jatoi, Zulifqar Ali Zaur, Imtiaz Ahmed Tago, Muhammad Asif Peracha, Niaz Hussain Keerio (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the efficiency of intra-articular platelet-rich plasma (PRP) injection in grade I and grade II osteoarthritis in the knee joints Study design: A longitudinal study Place and Duration: This study was conducted at Murshid Hospital and Health Care Center Karachi Pakistan from January 2021 to June 2021. Methodology: The ages of the patients were between 35 years and 65 years. All the patients were diagnosed with osteoarthritis of grade I and grade II. A total of 3 injections of PRP were injected intraarticular in the knees at an interval of 4 weeks. Patients were asked to come for a follow-up in the outpatient department. They were assessed for physical mobility and pain related to arthritis using the WOMAC score. The assessment was done when the treatment was given and after 6 months. Results: A total of 250 patients were considered in the present study. The mean age of the patients was 55.63±5.65 years. The ratio of disease in females to males was 3:1. A total of 178 patients had grade I osteoarthritis and 72 patients had grade II osteoarthritis according to Kellgren–Lawrence classification. A total of 210 patients had reported experiencing symptoms for less than 2 years and the remaining 40 had been experiencing the symptoms for more than 2 years. The mean WOMAC score was 82.9 before the treatment was started and it was 39.15 after 6 months of the treatment. The improvement of WOMAC score was more in the patients having symptoms for less than 2 years. Minor hyperemia was seen in 4 patients and those patients were managed conservatively by ice application and activity limitation. None of the patients showed signs of infection. Conclusion: The intraarticular injection of PRP proved to be beneficial and effective in the treatment of grade I and grade II early osteoarthritis.